Aplikasi Edukasi Jenis Narkoba Berbasis Augmented Reality Sebagai Media Pembelajaran Bagi Generasi Muda - Achmad Fauzi Makarim; Cindy Taurusta (LPPM UBHINUS MALANG, 2025)
Drugs are a serious threat to public health, especially the younger generation. Drug education has been carried out by the national narcotics agency but the reduction is not optimal, so a technology known as Augmented Reality (AR) is needed. The aim of research on educational applications on types of drugs for the young generation based on Augmented Reality is to make it easier for the young generation to understand about drugs and make users more interactive and interesting. This research was developed using the Multimedia Development Life Cycle research method. This method has six stages starting from the concept to the distribution results of the applications that have been created. From the research stages that have been carried out, the results of the Augmented Reality Education application on the types and side effects of drugs were obtained. This application still has limitations on Samsung Android devices. It doesn't support the Easy AR plugin. This application was created using the Markless Bassed Tracking method and uses black box testing with a very good category. This application can be used for education for the younger generation and the wider community.